Quantifying the effectiveness of private land conservation areas in preventing losses of natural land cover and biodiversity intactness across South Africa - Shumba, Tafadzwa (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.